STRATEGI PENGELOLAAN ZAKAT, INFAK DAN SEDEKAH (ZIS) PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS)KABUPATEN BALANGAN - Mahrini Mahrini; Meytri Meytri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Here is the translation of the text into academic and professional English, suitable for a thesis or research report: The research findings demonstrate that the zakat management strategies implemented by BAZNAS in Balangan Regency include: conducting both direct and indirect socialization, and compiling financial reports. Furthermore, zakat management at BAZNAS Balangan Regency is based on the principles of: Islamic sharia, trustworthiness, benefit, justice, legal certainty, integration, accountability in management, and transparency in managing ZIS (Zakat, Infaq, and Alms) through print media publications. This analysis is based on a logic that can maximize strengths and opportunities, while simultaneously minimizing weaknesses and threats. However, BAZNAS Balangan Regency still faces a constraint: the lack of public understanding regarding zakat.